(untitled) (International Journal of Innovative Technologies in Economy, 2019)
The rapid significant increase in the quality of the process of passenger transportation by Kyiv public transport can be a powerful motivation to increase the frequency of its use. However, the parameters of the desired change in the quality of urban transport remain unknown, which leads to its chaotic management. Two trends in urban passenger traffic quality research are common. The first approach deals with measuring the operating parameters of the transport system, and the second one focuses on the research of customers’ opinions regarding transport services. However, none of the scientists focuses fully on the specific human behavioral responses to the quality of the city’s passenger transportation service, when urban transport is opposed to a private car. Because of this, the assessment of the quality of urban passenger transport requires the development of special tools. It is already clear today that not all traditional approaches used in studies of transport behavior that depend on the quality structure may be suitable for this.